Regional cluster policies in Germany: Challenges, impacts and evaluation practices - Kiese, Matthias (Springer Nature, 2020)
Over the past two decades, the cluster concept has become ﬁrmly established in regional and innovation policy, as well as regional and local economic development at all spatial levels across Germany. The coming of age of such cluster policies shifts the focus of academic interest to the assessment of their outcomes. This paper seeks to contribute to the growing literature on cluster-policy evaluation in three ways: ﬁrstly, it focuses on regional cluster policies below the level of federal states in Germany to complement the majority of studies on federal and state-level programmes. Secondly, it adopts a publicchoice perspective, whereas most existing research concentrates on methodological and conceptual issues associated with cluster-policy evaluation. Thirdly, this paper attempts to see cluster policies as a whole by linking evaluation with the practices of policy design and implementation, which are interconnected in the policy cycle. Following a brief overview of regional cluster policies in Germany, we summarise the challenges, impacts and evaluation practices of seven case studies on a regional scale, i.e. below the level of federal states. Arguing that causal effects of such policies are difﬁcult to measure, we suggest that the real impacts are rather qualitative improvements in regions’ organisational capacities, whereas independent evaluations not primarily serving to legitimise political decisions require more active engagement by the academic community.